The Effect of Diversification Strategy, Profitability, and Leverage on Stock Returns of European Football Clubs - Huda Aulia Rahman; Lucia Ari Diyani; Surya Hadi Kurniawan (JURNAL ONLINE INSAN AKUNTAN, 2026)
This study focuses on a sample of football clubs listed on public stock exchanges in Europe during the period 2021 to 2024. Data analysis was conducted using multiple linear regression techniques using SPSS version 26 software. The study findings revealed that diversification strategy has a significant positive impact on stock returns. Furthermore, profitability also shows a positive correlation with stock returns. Conversely, leverage was found to have a negative effect on stock returns, indicating that higher debt levels are associated with lower returns for investors. This study contributes to the literature on the determinants of stock returns in football clubs, an area that remains under-researched. The empirical findings demonstrate that all independent variables—diversification strategy, profitability, and leverage—significantly influence stock returns. However, expanding the research population to include all publicly traded football clubs globally may yield different conclusions. A limitation of this study is the small sample size, given that only a limited number of football clubs in Europe are publicly listed. Additionally, the observation period is restricted to only four years.